2009
DOI: 10.4269/ajtmh.2009.81.235
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Lymphocytic Myocarditis in Baboons Is Associated with Trypanosoma cruzi Infection

Abstract: Non-specific lymphocytic myocarditis (NLM) is frequently observed in baboons within the endemic range of Trypanosoma cruzi. We sought to determine whether T. cruzi infection is a cause of baboon NLM. We evaluated serial histologic sections of cardiac muscle, blood cultures, immunohistochemistry, serology, polymerase chain reaction, and clinical pathology from 31 baboons with NLM to determine whether T. cruzi infection is associated with NLM. Eleven baboons with no evidence of T. cruzi infection by serology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…A previous study from our institute reported an association between nonspecific lymphocytic myocarditis and T. cruzi serology positivity in baboons 29 ; our results further confirm that association and extend it to our cynomolgus monkey colony.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study from our institute reported an association between nonspecific lymphocytic myocarditis and T. cruzi serology positivity in baboons 29 ; our results further confirm that association and extend it to our cynomolgus monkey colony.…”
Section: Discussionsupporting
confidence: 91%
“…cruzi infections have been reported in a number of New World species including marmoset, squirrel, spider, cebus, and woolly monkeys, and Old World species including baboons, macaques, and great apes (Williams et al, 2009;Andrade et al, 2009;Mubiru et al, 2014;Kunz et al, 2002). cruzi infections have been reported in a number of New World species including marmoset, squirrel, spider, cebus, and woolly monkeys, and Old World species including baboons, macaques, and great apes (Williams et al, 2009;Andrade et al, 2009;Mubiru et al, 2014;Kunz et al, 2002).…”
Section: A Pathogenesismentioning
confidence: 99%
“…Animals with anomaly-related mortality were more likely to have died (9, 75.0%) than to have been euthanized. The most common anomalies encountered were aortic aneurism rupture (5), atrial septal defect (2), and patent foramen ovale (2). Other anomalies seen once each were cardiac dysplasia, pulmonary artery stenosis, persistent ductus arteriosus, and tetrology of Fallot.…”
Section: Cardiovascular Systemmentioning
confidence: 99%